2022
DOI: 10.1007/s12144-022-02764-1
|View full text |Cite
|
Sign up to set email alerts
|

The parental career-related behaviors questionnaire (PCB): Psychometric properties in adolescents and young adults in the Italian context

Abstract: Over the last few years, the role of parental career-related behaviors in career development has been identified in several studies. Specifically, these behaviors involve difficulties in the adolescents' career decision-making. In the literature, there is a validated scale for measuring parental career-related behaviors in the Italian language, but the validation refers to the Swiss context. Thus, the present study aimed to test the psychometric proprieties of the parental career-related behaviors questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In line with previous researches [ 83 , 84 ], the first study was aimed to explore the structure of the WSSQ. In line with its original validation study [ 17 ], the exploration of the factorial structure of the WSSQ (Study1) indicated the presence of two factors (“Self-devaluation” and “Fear of enhanced stigma”) accounting for 55.04% of variance Moreover, items’ significant cross-loadings were lower than the threshold of 0.3—confirming this factorial solution.…”
Section: Discussionmentioning
confidence: 96%
“…In line with previous researches [ 83 , 84 ], the first study was aimed to explore the structure of the WSSQ. In line with its original validation study [ 17 ], the exploration of the factorial structure of the WSSQ (Study1) indicated the presence of two factors (“Self-devaluation” and “Fear of enhanced stigma”) accounting for 55.04% of variance Moreover, items’ significant cross-loadings were lower than the threshold of 0.3—confirming this factorial solution.…”
Section: Discussionmentioning
confidence: 96%
“…Starting from this background, in line with previous researches (Panzeri et al, 2021c;Parola et al, 2022;Rossi et al, 2022), the aim of the first study here reported was to extensively examine the factorial structure of the PDI. To achieve this goal, EGA was used: an innovative technique, particularly precise and sensitive in identifying the correct number of factors/dimensions (Golino and Epskamp, 2017).…”
Section: Discussionmentioning
confidence: 86%
“…On the other hand, it is important to test the psychometric properties of the instruments with a population in the same language, but with a different context (Parola et al, 2022). Especially in countries that have different characteristics, such as Peru (Caycho-Rodriíguez et al, 2018) and to get closer to a bias-free measurement (Pendergast et al, 2017).…”
Section: Discussionmentioning
confidence: 99%